NETmundial: only a landmark event if 'Digital Cold War' rhetoric abandoned - Francesca Musiani; Julia Pohle (Internet Policy Review, 2014)
While internet privacy has been a central concern for quite a long time, the revelations by Edward Snowden about the US National Security Agency's massive surveillance programme have highlighted the extent to which it is a core political issue. The privacy-surveillance controversy has prompted what is perhaps the most prominent and ambitious call in internet governance history to break the dominance of the United States' control over internet infrastructure: the Global Multistakeholder Meeting on the Future of Internet Governance, or NETmundial (April 2014). The article analyses the current state of multi-stakeholderism in internet governance in light of this event. In particular, it argues for the necessity to leave the 'Digital Cold War' rhetoric behind if the internationalisation and the globalisation of internet governance is to move to the next level.
Keywords: 300; Internet governance; Multi-stakeholderism; Net Mundial; Digital Cold War; United States of America